Pengaruh Unggahan Dari Content Creator Program Afiliasi E-Commerce Shopee Terhadap Minat Beli - Andini Dwi Yanti Sutarman; Oky Oxcygentri; Rastri Kusumaningrum (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research discusses the effect of uploads from content creators of the Shopee e-commerce affiliate program on purchase intention (multiple linear regression analysis of Indonesian Shopee consumers on Instagram social media). The theory used is the AIDA theory in which there are four sub dimensions which include Attention, Intention, Desire and Action. The research design in this study was qualitative with the sample population taken from 94 Communication Science students at Singaperbangsa Karawang University class of 2019 with the sampling taken using the Non Probability Sampling method with the aggregation method. Purposive and Snowball Sampling. The results of the research and discussion show that the Independent Variables (Awareness, Intention, Desire and Action) have a significance or influence on the Purchase Intention Variable by calculating the results of R2 which has a yield magnitude of 0.143 or 14.3%. which means that the Independent Variables (Awareness, Intention, Desire and Action) have an impression on the dependent variable (Purchasing Interest) with a value of 14.3% and the contribution of other variables not examined is 85.7%.